Dwellers Characteristics and their Influence on Urban Green Areas, Chilca, Lima - Malca-Casavilca, Nora (2021)
The aim of this research was to know the interaction from the cultural, economic-social and distribution of green spaces in Chilca. The research is basic, not experimental, to collect data the survey was used, which was applied in the field for 24 months. The results showed that, despite changes due to industrial development in the distribution of green spaces, the cultural vision and the socio-economic characteristics do not influence in the green spaces of the district. It was remarkable hearing from some dwellers their knowledge about zoning and how useful it would be to develop projects in the district based on it to recover and conserve their natural spaces.